INVESTIGATION OF STRENGTH PROPERTIES OF RADIATION-MODIFIED POLYMER COATINGS - Tojiboyev Begijon Mamitjonovich; Yakubjonov Fayzulloh Tursunali O‘G‘Li; Xojimatov Umidbek Turgʻunboy Oʻgʻli (The American Journal of Engineering and Technology, 2023)
One of the methods for improving the properties of polymer coatings is radiation treatment. It is mainly carried out by ultraviolet rays and ionizing radiation. There are several types of ionizing radiation: radiation caused by deep changes in the electron shell and the nucleus of the atom and having the nature of electromagnetic oscillations, x-ray and γ-radiation; streams of charged particles that can have both positive and negative charges.